Sideritis L. essential oils: A systematic review - Chrysargyris, Antonios; Tomou, Ekaterina Michaela; Goula, Katerina; Dimakopoulou, Konstantina; Tzortzakis, Nikos G.; Skaltsa, Helen (My University, 2023)
Essential oils are extensively used in the food, cosmetic, perfume, pharmaceutical, and agrochemical industries due to their aroma and pharmacological properties. The Lamiaceae family is mainly represented by widely well-known medicinal and aromatic plants that produce essential oil. Over the years, Sideritis L. essential oils have attracted great interest due to their chemical variability among the different taxa and their pharmacological activities. In-depth research of previously published literature was performed on electronic databases with several key search words for the collection of the available data and a total of 128 scientific studies were used since 1983. To date, 155 accepted Sideritis samples have been studied originating from 15 countries and more than 250 compounds have been reported in 87 Sideritis taxa overall. Furthermore, antimicrobial and antioxidant effects have been the most studied pharmacological activities. This review summarizes and critically discusses the research work on the chemical composition and pharmacological activities of essential oil of the genus Sideritis based on the currently valid taxonomy. Additionally, statistical analysis is encompassed to provide a deeper comprehensive understanding of the high chemical polymorphism of Sideritis essential oils. We expect that this review will encourage researchers to investigate unexplored Sideritis taxa and will contribute to revealing uncharted scientific territory and future perspectives on these plants.
Keywords: Chemical constituents; Essential oils; Lamiaceae; Pharmacological activities; Sections